Pengaruh Perputaran Arus Kas, Current Ratio, Debt to Asset Ratio dan Debt to Equity Ratio Terhadap Return on Asset pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia Tahun 2015-2022 - Budi Purnasari, Retno; Damayanti, Santi (Economic Reviews Journal, 2024)
The purpose of this study is to ascertain how return on assets in food and beverage manufacturing companies listed on the Indonesia Stock Exchange is impacted by cash flow turnover, current ratios, debt to equity ratios, and debt to asset ratios for the years 2015–2022. This study employs a quantitative methodology that combines a verification and descriptive strategy. While verification statistical analysis uses traditional assumption tests, multiple linear regression tests, Pearson product moment correlation coefficient tests, determination coefficient tests, and hypothesis testing with partial and simultaneous tests (t and f tests), descriptive statistical data analysis techniques are used to find mean, maximum, minimum, and standard deviation data. 56 financial reports from businesses in the Food and Beverage Manufacturing Companies provide the sample data. sampling utilizing nonprobability sampling methods combined with purposive sampling. IBM SPSS version 26.0 was the analysis tool used in this investigation. The study's findings indicate that return on assets is not affected partially or simultaneously by cash flow turnover, current ratio, debt to equity, or debt to asset ratio